Kajian Literatur Pastoral Konseling Pada Pemuda yang Mengalami Trauma Akibat Kehilangan Orangtua - Sumakul, Yunita; Cristhania; Ponto, Chanesa; Panese, Julaiedy; Ramenaung, Yesica (Universitas Pahlawan Tuanku Tambusai, 2025)
Losing parents is one of the most difficult experiences a young person can face. This event not only causes sadness but also triggers various complex forms of trauma, including emotional, psychological, social, spiritual, and developmental trauma. The trauma arising from such loss can significantly impact the mental health, social relationships, beliefs, and life meaning of the affected youth. Therefore, a comprehensive and holistic approach to support is required, one that not only focuses on psychological aspects but also addresses spiritual and social dimensions. Pastoral counseling serves as a form of accompaniment that integrates emotional support and spiritual values in the process of trauma recovery. Through this approach, pastoral counselors not only listen to the complaints and pain experienced by the youth but also provide strengthening of faith and hope, helping them find new meaning in life. The pastoral counseling process involves several important steps, such as building an empathetic relationship, providing a safe space for sharing, instilling hope through spiritual values, and reinforcing community support. Thus, the process of healing from trauma due to grief or parental loss can be conducted comprehensively, covering emotional, psychological, social, and spiritual aspects, enabling youth to live their lives with renewed resilience and enthusiasm.